A Guide to border control and patrol - Alison Knapp (Congressional policies, practices and procedures series., 2019)
The government reports included in this book range from June to September 2018 and examine US border control and security. The first report is focused on the Department of Homeland Security. The Department of Homeland Security (DHS) was established by the Homeland Security Act of 2002 and began operations in 2003. This report examines the Department of Homeland Security's (DHS) Office of Strategy, Policy and Plans as well as its Sub-Offices. The second report is an assessment of selected DHS components requirements infrastructure (such as Customs and Border Protection, Federal Emergency Management Agency, the US Coast Guard, and the US Citizenship and Immigration Services). It provides recommendations on additional practices that could help better develop operational requirements. Next, the southwest border of the United States has long been vulnerable to cross-border illegal activity. According to Border Patrol data, in Fiscal year 2017, Border Patrol agents apprehended 304,000 illegal entrants. Additionally, the US Customs and Border Protection's (CBP) spent approximately $2.3 billion between 2007 and 2015 to deploy physical barriers along the nearly 2,000-mile southwest border. In the third report, the progress DHS has made is examined as well as the challenges it has faced implementing its border security efforts. In January and March 2017, the President issues a series of executive orders related to border security and immigration. The fourth report included in this book reviews the agencies' implementation of the executive orders and related spending. Finally, the processes for tracking and unifying separated families are looked at and the progress and challenges in recruiting, hiring and retaining law enforcement personnel for US Customers and Border Protection is discussed in detail.